PENGARUH PENEMPATAN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI PADA RUMAH SAKIT JIWA TAMPAN KOTA PEKANBARU - Apriliani, Chintya; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to determine the effect of job placement and work experience on employee performance at Tampan Mental Hospital, Pekanbaru City partially and simultaneously. This study used a questionnaire as a data collection tool distributed to 73 respondents. The data analysis technique used is multiple linear regression, hypothesis testing, and determination keofisien using SPSS 16. 16. Based on the results of the research, job placement partially affects the performance of employees at the Tampan Mental Hospital, Pekanbaru City. Work experience partially affects employee performance at Tampan Mental Hospital, Pekanbaru City. Job placement and work experience simultaneously or together affect the performance of employees at the Tampan Mental Hospital, Pekanbaru City. Keywords: Job Placement, Work Experience, Performance.